Enzyme activities and morphological appearance in functioning and excluded segments of the small intestine after shunt operation for obesity. Issue 7 (July 1979) - Asp, N G; Gudmand-Høyer, E; Andersen, B; Berg, N O
Abstract : Five patients in whom small-intestinal bypass was performed for severe obesity had a second operation 11-19 months later because of insufficient weight loss. Mucosal enzyme activities and histological appearance were investigated in biopsies from different parts of the functioning and excluded small intestine. These were compared with biopsies form corresponding sites obtained at the first operation. In addition to a prominent increase in length, circumference, and mucosal thickness in the functioning shunt, the disaccharidases and two intracellular beta-galactosidases increased in specific activity, , especially in the distal ileal part of the shunt. In the excluded segment of the small intestine different enzymes showed a different response: trehalase increased and alkaline phosphate decreased significantly. Other enzymes that were measured showed a varied pattern. The results indicated that not only the luminal content but also other, presumably hormonal, factors regulated the enzyme activities, and that different regulating factors influenced the various enzymes differently. The marked adaptive increase in mucosal surface of the functioning shunt could be one factor in explaining the weight stabilisation and, in some cases, weight increase after the initial rapid weight loss after the operation for small-intestinal bypass. The increase in specific enzyme activities would further increase the digestive capacity of the shunt.